2006
DOI: 10.1038/sj.jcbfm.9600169
|View full text |Cite
|
Sign up to set email alerts
|

Free Radical-Mediated Damage to Barrier Function is not Associated with Altered Brain Morphology in High-Altitude Headache

Abstract: The present study combined molecular and neuroimaging techniques to examine if free radical-mediated damage to barrier function in hypoxia would result in extracellular edema, raise intracranial pressure (ICP) and account for the neurological symptoms typical of high-altitude headache (HAH) also known as acute mountain sickness (AMS). Twenty-two subjects were randomly exposed for 18 h to 12% (hypoxia) and 21% oxygen (O2 (normoxia)) for collection of venous blood (0 h, 8 h, 15 h, 18 h) and CSF (18 h) after lumb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
108
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(117 citation statements)
references
References 47 publications
9
108
0
Order By: Relevance
“…However, in AMS, lumbar punctures reveal an intact blood-brain barrier for large molecular weight proteins [38]. Furthermore, there are no significant associations of peripheral oedema [39], slight increase in brain volume [14], albuminuria [40] and leakage of fluorescent dye from retinal vessels [41] with AMS.…”
Section: Hypoxaemiamentioning
confidence: 99%
See 1 more Smart Citation
“…However, in AMS, lumbar punctures reveal an intact blood-brain barrier for large molecular weight proteins [38]. Furthermore, there are no significant associations of peripheral oedema [39], slight increase in brain volume [14], albuminuria [40] and leakage of fluorescent dye from retinal vessels [41] with AMS.…”
Section: Hypoxaemiamentioning
confidence: 99%
“…Direct measurements indicate that ICP appears to be normal in subjects with AMS at rest [38,44], but may increase with exercise or other factors that increase blood or intrathoracic pressure [45], due to decreased intracranial compliance. Disturbed autoregulation may occur in AMS [35,46] and could enhance pressure transduction to the brain, although findings are controversial [47].…”
Section: The Brainmentioning
confidence: 99%
“…Subsequently, we explored the relationship between the development of a specific acute mountain sickness symptom, headache, with changes in brain water mobility and content after 2 hours (presymptomatic) and 10 hours (symptomatic) in hypoxia. Given the lack of molecular evidence for breakdown of the bloodbrain barrier in hypoxia, 10,11 but evidence for the accumulation of both extracellular and intracellular water, 3,4,8 we hypothesized that early hypoxia (2 hours) will be characterized by a reduction in mean diffusivity and increased fractional anisotropy but no change in T 2 in line with a fluid shift into the intracellular space. In contrast, more prolonged hypoxia (10 hours) will be associated with reduced mean diffusivity but increased fractional anisotropy and T 2 , which would suggest an increase in brain edema.…”
Section: Introductionmentioning
confidence: 99%
“…Sequential study designs are also used to a great extent in investigations of hypoxia by exposure in chambers or masks (42)(43)(44)(45)(46), but there are also well-controlled studies (47)(48)(49)(50)(51). Four of the well-controlled studies reported a relationship between exposure to hypoxia and oxidative damage to both DNA and lipids (47,48,50,51), whereas one investigation found no effect of hypoxia (49). Data based on sequential studies indicate hypoxia-induced effects on at least one biomarker of lipid or DNA oxidation (12-16, 20, 23, 24, 34-42, 45, 46), except two studies that happens to be short-term (less than 10 min) exposure to hypoxia (43,44).…”
Section: Methodsmentioning
confidence: 99%
“…For instance, oxygen level decreased over time in studies of the ascend to the summit of San Pedro y San Pablo volcano (46) and the simulated ascend to Mt Everest (37), but it is impossible to split the time component from the effect of hypoxia. Figure 1 outlines the results of an overall analysis where studies have been stratified into those with exposures lasting 1 h or less (43)(44)(45)48), between 1 and 24 h (16,42,46,47,50,51), and between 24 h and 8 weeks (12-16, 20, 23, 34-41). This analysis indicates that the effect observed after days or weeks of hypoxia is larger than at earlier time point, but it should also be recognized that most of these studies are poorly controlled and it may just be an effect of confounding factors.…”
Section: Dose-response Relationshipmentioning
confidence: 99%